A-Site Excess (La0.8Ca0.2)1.01FeO3−δ (LCF) Perovskite Hollow Fiber Membrane for Oxygen Permeation in CO2-Containing Atmosphere - Yang, D.; Yang, N.; Meng, B.; Tan, X.; Zhang, C.; Sunarso, J.; Zhu, Z.; Liu, Shaomin (American Chemical Society, 2017)
CO 2 -resistant oxygen selective ceramic membranes show potential to be utilized in clean combustion and membrane-based reactions for greener chemical synthesis. In real applications, such membranes should have high mechanical strength as well as high oxygen flux and high stability in a CO 2 -containing atmosphere. In this work, a (La 0.8 Ca 0.2 ) 1.01 FeO 3-d (LCF) perovskite hollow fiber membrane was developed. Its oxygen permeation behavior was tested in different gas atmospheres, i.e., helium and carbon dioxide. Compared to the typical perovskite hollow fibers such as La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3 (LSCF) and Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-d (BSCF), the LCF hollow fiber displayed the highest mechanical strength as well as the largest oxygen fluxes and stability in a CO 2 -containing atmosphere, highlighting its attractiveness in oxyfuel combustion and syngas production from methane.